Characterization of Conserved T- and B-Cell Epitopes in Plasmodium falciparum Major Merozoite Surface Protein 1 - Parra, Marcela (American Society for Microbiology, 2000)
Vaccines for P. falciparum will need to contain both T- and B-cell epitopes. Conserved epitopes are the most desirable, but they are often poorly immunogenic. The major merozoite surface protein 1 (MSP-1) is currently a leading vaccine candidate antigen. In this study, six peptides from conserved or partly conserved regions of MSP-1 were evaluated for immunogenicity in B10 congenic mice. Following immunization with the peptides, murine T cells were tested for the ability to proliferate in vitro and antibody responses to MSP-1 were evaluated in vivo. The results showed that one highly conserved sequence (MSP-1#1, VTHESYQELVKKLEALEDAV; located at amino acid positions 20 to 39) and one partly conserved sequence (MSP-1#23, GLFHKEKMILNEEEITTKGA; located at positions 44 to 63) contained both T- and B-cell epitopes. Immunization of mice with these peptides resulted in T-cell proliferation and enhanced production of antibody to MSP-1 upon exposure to merozoites. MSP-1#1 stimulated T-cell responses in three of the six strains of mice evaluated, whereas MSP-1#23 was immunogenic in only one strain. Immunization with the other four peptides resulted in T-cell responses to the peptides, but none of the resulting peptide-specific T cells recognized native MSP-1. These results demonstrate that two sequences located in the N terminus of MSP-1 can induce T- and B-cell responses following immunization in a murine model. Clearly, these sequences merit further consideration for inclusion in a vaccine for malaria.